PELATIHAN PROSES GAS METAL ARC WELDING (GMAW) UNTUK TUKANG LAS SOLO RAYA - Triyono; Nurul Muhayat; Eko Surojo (Pusat Penelitian dan Pengabdian Masyarakat, 2026)
There are numerous welding workshops in Solo, but they mostly offer similar products such as household items like fences, canopies, and window grilles. These products are customized, leading to inconsistent production levels—sometimes with high demand, other times quiet periods. To sustain these workshops, it's crucial to innovate both products and marketing strategies. Products like office, campus, and school furniture are consistently in demand. To compete effectively, workshop products need to improve in quality through advanced welding technology, particularly Gas Metal Arc Welding (GMAW). Therefore, workshops require training in using sophisticated equipment like GMAW machines. In the Community Partnership Program (PKM), the PKM UNS team collaborates with two partners: Sumber Rejeki Welding Workshop in Dusun Sawahan and the Takmir of Fatimah Ar-Royyan Mosque. The program unfolds in two phases. Phase I involves training workshop owners and workers in GMAW machine operations, with the PKM UNS team providing expertise. Phase II includes a joint project to create desk and chair furniture as demonstration products from the training, which will be donated to the TPA of Fatimah Ar-Royyan Mosque in Jongkang. This PKM initiative aims to equip owners and workers from Sumber Rejeki Welding Workshop and nearby workshops with skills in designing structures and manufacturing office furniture using GMAW, as well as effectively marketing these products.